Marketing medicines: charting the rise of modern therapeutics through a systematic review of adverts in UK medical journals (1950–1980) - Green, A; Haddad, P; Aronson, J (Wiley, 2018)
Aims To examine how pharmaceutical products that were first marketed between 1950 and 1980 were promoted to physicians through advertisements and briefly review advertising regulations and accuracy of the advertisements in the light of modern knowledge. Methods We systematically reviewed advertisements promoting drugs for specific therapeutic areas, namely central nervous system disorders (anxiety and sleep disorders, depression, psychoses, and Parkinson's disease), respiratory disorders, cardiovascular disorders, and gastrointestinal disorders. We examined about 800 issues of the British Medical Journal (1950–1980) and about 150 issues of World Medicine (1965–1984). Results Advertising material was minimally regulated until the mid‐1970s. Many drugs were marketed with little preclinical or clinical knowledge and some with the expectation that prescribers would obtain further data. The peak of advertising occurred in parallel with the surge in the release of novel drugs during the 1960s, but declined markedly after the mid‐1970s. Advertisements generally contained little useful prescribing information. The period we investigated saw the release of many novel pharmaceuticals in the therapeutic areas we examined, and many (or their class successors) still play important therapeutic roles, including benzodiazepines, tricyclic antidepressants, phenothiazines, levodopa, selective and non‐selective β‐adrenoceptor antagonists, thiazide diuretics, β‐adrenoceptor agonists, and histamine H2 receptor antagonists. Conclusions Advertising pharmaceuticals in the BMJ and World Medicine in 1950–1980 was poorly regulated and often lacked rigour. However, advertisements were gradually modified in the light of increasing clinical pharmacological knowledge, and they reflect an exciting period for the introduction of many drugs that continue to be of benefit today.